Evaluating the efficacy of a standardized 4 mL/kg fluid bolus technique in critically ill patients with elevated PvaCO2: secondary analysis of two prospective studies - Attou, Rachid; Du, Thierry; Velissaris, Dimitrios; Redant, Sebastien; Talpoș, Mircea T.; Pierrakos, Charalampos (Frontiers in Medicine, 2024)
Background: Limiting the fluid bolus (FB) volume may attenuate side effects, including hemodilution and increased filling pressures, but it may also reduce hemodynamic responsiveness. The minimum volume to create hemodynamic effects is considered to be 4 mL/kg. In critically ill patients, the hemodynamic effects of FB with this volume have not been adequately investigated and compared to higher quantities. We hypothesized that a standardized FB approach using 4 mL/kg has comparable hemodynamic and metabolic effects to the common practice of physician-determined FB in critically ill patients.Methods: We conducted post hoc analysis of two trials in non-selected critically ill patients with central venous-to-arterial CO2 tension (PvaCO2) >6 mmHg and no acute bleeding. All patients received crystalloids either at a physician-determined volume and rate or at 4 mL/kg pump-administered at 1.2 L/h. Cardiac index (CI) was calculated with transthoracic echocardiogram, and arterial and venous blood gas samples were assessed before and after FB. Endpoints were changes in CI and oxygen delivery (DO2) >15%.Results: A total of 47 patients were eligible for the study, 15 of whom received physician-determined FB and 32 of whom received standardized FB. Patients in the physician-determined FB group received 16 (12-19) mL/kg at a fluid rate of 1.5(1.5-1.9) L/h, compared to 4.1 (3.7-4.4) mL/kg at a fluid rate of 1.2 (1.2-1.2) L/h (p < 0.01) in the standardized FB group. The difference in CI elevations between the two groups was not statistically significant (8.8% [-0.1-19.9%] vs. 8.4% [0.3-23.2%], p = 0.76). Compared to physician-determined FB, the standardized FB technique had similar probabilities of increasing CI or DO2 by >15% (odds ratios: 1.3 [95% CI: 0.37-5.18], p = 0.66 and 1.83 [95% CI: 0.49-7.85], p = 0.38).Conclusions: A standardized FB protocol (4 mL/kg at 1.2 L/h) effectively reduced the volume of fluid administered to critically ill patients without compromising hemodynamic or metabolic effects.